Interaction of Mycobacteria With Host Cell Inflammasomes - Rastogi, Shivangi; Briken, Volker (Frontiers in Immunology, 2022)
The inflammasome complex is important for host defense against intracellular bacterial infections. Mycobacterium tuberculosis (Mtb) is a facultative intracellular bacterium which is able to survive in infected macrophages. Here we discuss how the host cell inflammasomes sense Mtb and other related mycobacterial species. Furthermore, we describe the molecular mechanisms of NLRP3 inflammasome sensing of Mtb which involve the type VII secretion system ESX-1, cell surface lipids (TDM/TDB), secreted effector proteins (LpgH, PPE13, EST12, EsxA) and double-stranded RNA acting on the priming and/or activation steps of inflammasome activation. In contrast, Mtb also mediates inhibition of the NLRP3 inflammasome by limiting exposure of cell surface ligands via its hydrolase, Hip1, by inhibiting the host cell cathepsin G protease via the secreted Mtb effector Rv3364c and finally, by limiting intracellular triggers (K+ and Cl- efflux and cytosolic reactive oxygen species production) via its serine/threonine kinase PknF. In addition, Mtb inhibits the AIM2 inflammasome activation via an unknown mechanism. Overall, there is good evidence for a tug-of-war between Mtb trying to limit inflammasome activation and the host cell trying to sense Mtb and activate the inflammasome. The detailed molecular mechanisms and the importance of inflammasome activation for virulence of Mtb or host susceptibility have not been fully investigated.